Development of a model for particulate matter pollution in Australia with implications for other satellite-based models - Pereira, Gavin; Lee, H.; Bell, M.; Regan, Annette; Malacova, Eva; Mullins, Ben; Knibbs, L. (Academic Press, 2017)
Estimating exposure to particulate matter (PM10) air pollution concentrations in Australia is challenging due to relatively few monitoring sites relative to the geographic distribution of the population. We modelled daily ground-level PM10 concentrations for the period 2006–2011 for Australia using linear mixed models with satellite remote-sensed AOD, land-use and geographical variables as predictors. The variation in daily PM10 explained by the model was 51% for Australia overall, and ranged from 51% for Tasmania to 78% for South Australia. Cross-validation indicated that the models were most suitable for prediction in New South Wales and Victoria and least suitable for prediction in Western Australia, the Australian Capital Territory and Tasmania. Most of the variation in PM10 concentrations was explained by temporal rather than spatial variation. The inclusion of AOD and other predictors did not substantially improve model performance. Temporal models were sufficient to account for daily PM10 variation recorded by statutory monitors.